High frequency active high-pass filter used distributed MOSFET - Pirajnanchai, Virote; Janchitrapongvej, Kanok; Panyanouvong, Nouanchanh (My University, 2005)
In many signal processing situations, filters must interface with the real world where the input and output signal take on continuous values functions of the continuous variable time, In this paper describes a new high frequency continuous-time high-pass filter. The filter is realized for converting an active distributed RC to a transistor-only high pass filter circuit. The frequency response of high-pass was examined by a MOSFET model. Preliminary experimental simulation results by PSpice programs for high frequency high-pass filter is presented. © 2005 IEEE.
Keywords: Active filter; Continuous-time filters; VHF filter distributed RC filter